Demonstration of Gut-Barrier Dysfunction in Early Stages of Non-alcoholic Fatty Liver Disease: A Proof-Of-Concept Study - Kaushal, Kanav; Agarwal, Samagra; Sharma, Sanchit; Goswami, Pooja; Singh, Namrata; Sachdev, Vikas; Poudel, Shekhar; Das, Prasenjit; Yadav, Rajni; Kumar, Dinesh; Pandey, Gaurav; Gunjan, Deepak; et al. (Journal of clinical and experimental hepatology, 2022)
Gut-barrier dysfunction is well recognized in pathogenesis of both non-alcoholic fatty liver disease (NAFLD) and alcoholic liver disease (ALD). However, comparison of components of this dysfunction between the two etiologies remains unexplored especially in early stages of NAFLD. Components of gut-barrier dysfunction like alterations in intestinal permeability (IP) by lactulose mannitol ratio (LMR) in urine, systemic endotoxemia (IgG and IgM anti-endotoxin antibodies), systemic inflammation (serum tumor necrosis factor alpha [TNF-α] and interleukin-1 [IL-1] levels), tight junction (TJ) proteins expression in duodenal biopsy and stool microbiota composition using Oxford Nanopore MinION device were prospectively evaluated in patients with NAFLD (n = 34) with no cirrhosis, ALD (n = 28) and were compared with disease free controls (n = 20). Patients with ALD had more advanced disease than those with NAFLD (median liver stiffness -NAFLD:7.1 kPa [5.9–8.9] vs. ALD:14.3 kPa [9.6–24], P < 0.001]. Median LMR was significantly higher in NAFLD and ALD group when compared to controls (NAFLD 0.054 [0.037–0.17] vs. controls 0.027 [0.021–0.045] (P = 0.001)) and ALD 0.043 [0.03–0.068] vs. controls 0.027 [0.021–0.045] (P = 0.019)]. Anti-endotoxin antibody titer (IgM) (MMU/mL) was lowest in NAFLD 72.9 [3.2–1089.5] compared to ALD 120.6 [20.1–728]) (P = 0.042) and controls 155.3 [23.8–442.9]) (P = 0.021). Median TNF-α (pg/mL) levels were elevated in patients with NAFLD (53.3 [24.5–115]) compared to controls (16.1 [10.8–33.3]) (P < 0.001) and ALD (12.3 [10.1–42.7]) (P < 0.001). Expression of zonulin-1 and claudin-3 in duodenal mucosa was lowest in NAFLD. On principal co-ordinate analysis (PCoA), the global bacterial composition was significantly different across the three groups (PERMANOVA test, P < 0.001). While remaining activated in both etiologies, gut-barrier dysfunction abnormalities were more pronounced in NAFLD at early stages compared to ALD despite more advanced disease in the latter.